Sengketa Pemilihan Umum dan Implikasinya terhadap Stabilitas Ketatanegaraan di Indonesia - Syahrul Nugraha Baderung; Sity Rahma Polinggapo; Roy Marthen Moonti (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
Electoral disputes are a frequent phenomenon in the democratic process, especially in Indonesia. This article analyzes various aspects of electoral disputes, including their causes, impacts and existing resolution mechanisms. These disputes usually arise as a result of alleged violations, fraud or dissatisfaction with election results, which can trigger political tensions and undermine public confidence in the democratic system. This research shows that electoral disputes not only affect the outcome of elections, but also have far-reaching implications for constitutional stability, including the potential for social conflict and government legitimacy. Through a normative approach, this article explores the role of the Constitutional Court as an institution authorized to resolve disputes over election results. It also highlights the importance of transparency and fairness in the electoral process to prevent disputes. In addition, the article proposes strategic measures to improve electoral integrity, such as the strengthening of oversight institutions and political education to the public. Thus, it is hoped that the resolution of electoral disputes can be carried out effectively to maintain political stability and the sustainability of democracy in Indonesia.